Pembentukan Citra Merek Minimarket Melalui Viral Marketing (Studi Kasus Minimarket 212) - Yulia Hamdaini Putri; Dessy Yunita; Aslamia Rosa (Falah: Jurnal Ekonomi Syariah, 2019)
Brand image is one of the important aspects of marketing, this also happens to the 212 minimarkets which is being discussed lately. The aims of this study are to understand the role of viral marketing on the formation of brand images and interest in shopping at minimarket 212. This study is qualitative using questi0nonaire as the method of data collection. The population of this research is the general population of Palembang aged 16-69 years who have sufficient knowledge of 212 minimarkets. The result of this study, are as follows: first, that viral marketing has a significant effect on the brand image (Est: 0.426; SE: 0.033; CR: 0.033; P: 000). Second, that viral marketing has a significant effect on behavioral intentions (Est: 0.261; SE: 0.040; CR: 6.538; P: 0.000). Third, that brand image has a significant effect on behavioral intentions (Est: 1,187; SE: 0,067; CR: 17,708; P: 0,000). Thus, the effect of viral marketing on shopping interest in a 212 minimarket has the smallest influence value among other variables which is only 0.26 point. However, with the brand image variable as an intervening variable, the effect is greater up to 0.50 point, this means that brand image which formed through viral marketing get a good response from the public to increase the willingness to shop.